3
$\begingroup$

I have put his on wolfram and obtained answer as follows:

$\sum_{n=1}^{\infty}\frac{n}{2^n} = 2$

And the series is convergent too because $\lim_{n\to\infty} \frac {n}{2^n} = 0$

However I am wondering if there is a convenient way to solve this; I don't think you can represent it by a geometric progression either. So how do we have to do it on paper?

$\endgroup$
  • 9
    $\begingroup$ Of course the fact that $\lim_{n \to \infty} \frac{n}{2^n} \to 0$ doesn't imply that the series is convergent. $\endgroup$ – Amateur Apr 17 '14 at 2:49
  • 2
    $\begingroup$ Differentiate the geometric series. $\endgroup$ – Bitrex Apr 17 '14 at 2:50
7
$\begingroup$

Let $S$ be our sum. Then $S=\frac{1}{2}+\frac{2}{2^2}+\frac{3}{2^3}+\frac{4}{2^4}+\cdots$. Thus $$\begin{align}2S&=1+&\frac{2}{2}+\frac{3}{2^2}+\frac{4}{2^3}+\frac{5}{2^4}+\cdots\\ S&=&\frac{1}{2}+\frac{2}{2^2}+\frac{3}{2^3}+\frac{4}{2^4}+\cdots\end{align} $$ Subtract. We get $$S=1+\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}+\cdots=2.$$

$\endgroup$
3
$\begingroup$

Hint:

$$ \sum_{k=1}^{\infty} x^k = \frac{x}{1-x} \implies \sum_{k=1}^{\infty} kx^k=\frac{d}{dx} \frac{x}{1-x} . $$

$\endgroup$
  • $\begingroup$ Want to understand why we can differentiate. $\endgroup$ – deostroll Apr 17 '14 at 4:14
  • 1
    $\begingroup$ @deostroll: We can differentiate a power series within its radius of convergence. $\endgroup$ – Mhenni Benghorbal Apr 17 '14 at 4:21
  • 2
    $\begingroup$ @deostroll The technical result allowing us to do this is the following: First, power series $\sum \alpha_n x^n$ converge absolutely and uniformly on any closed subset of their (open) interval of convergence. (This follows from the $M$-test.) Second, the (formal) series of their termwise derivative, $\sum n\alpha_n x^{n-1}$, has the same radius of convergence. (Cont.) $\endgroup$ – Andrés E. Caicedo Apr 19 '14 at 3:11
  • 2
    $\begingroup$ @deostroll Third, and this is the technical part, if a sequence $f_n$ of differentiable functions defined on some closed interval satisfies that (1) $f_n'\to g$ uniformly, and (2) $f_n(x_0)$ converges (as $n\to\infty)$ for some $x_0$, then (a) $f_n$ converges uniformly to some differentiable function $f$, and (b) $f'=g$. To apply this, take as $f_n$ the partial sums of the given power series. A proof of this theorem appears for instance in Rudin's Principles of mathematical analysis, see Theorem 7.17. (Cont.) $\endgroup$ – Andrés E. Caicedo Apr 19 '14 at 3:15
  • 1
    $\begingroup$ @deostroll The assumption is technical, but cannot really be relaxed: Even if we assume that $f_n\to f$ uniformly, that $f$ is differentiable, and that $f_n'\to g$ pointwise, we may have that $f'(x)\ne g(x)$ for all $x$. This is a (remarkably recent!) theorem of Darji, see here. $\endgroup$ – Andrés E. Caicedo Apr 19 '14 at 3:17
3
$\begingroup$

Another way to do the problem is to note that $$\left(\sum_{k=1}^\infty \frac{1}{2^k}\right)^2 = \sum_{k=1}^\infty \frac{k-1}{2^k}$$ so that the desired series is really just $$\left(\sum_{k=1}^\infty \frac{1}{2^k}\right)^2 + \sum_{k=1}^\infty \frac{1}{2^k}$$

$\endgroup$
1
$\begingroup$

If $\displaystyle S=\sum_{n=1}^\infty\frac{n}{2^n}$, then $$S-\frac12=\sum_{n=1}^\infty\frac{n+1}{2^{n+1}}=\frac12\sum_{n=1}^\infty\frac{n+1}{2^n}=\frac12\left(S+\sum_{n=1}^\infty\frac1{2^n}\right)=\frac12(S+1),$$ so $2S-1=S+1$, or $S=2$.

All that remains is to justify that the series converges. But $n<1.1^n$ for $n$ large enough, so a tail of $S$ is bounded above by a tail of the convergent geometric series $\sum_n\left(\frac{1.1}2\right)^n$.

$\endgroup$
0
$\begingroup$

In this answer we go for the 'one trick pony' approach - all we know is that for $k \ge 0$,

$\tag 1 \sum_{n=k}^{\infty}\frac{1}{2^n} = 2^{1-k}$

We decompose the summands of $\sum_{n=1}^{\infty}\frac{n}{2^n}$ in a natural/straightforward manner, arranging these numbers into a table:

$$\begin{pmatrix} \frac{1}{2} & \frac{1}{4} & \frac{1}{8} & \frac{1}{16} & \frac{1}{32} & \dots \\ 0 & \frac{1}{4} & \frac{1}{8} & \frac{1}{16} & \frac{1}{32} & \dots \\ 0 & 0 & \frac{1}{8} & \frac{1}{16} & \frac{1}{32} & \dots \\ 0 & 0 & 0 & \frac{1}{16} & \frac{1}{32} & \dots \\ 0 & 0 & 0 & 0 & \frac{1}{32} & \dots \\ 0 & 0 & 0 & 0 & 0 & \dots \\ . \\ . \\ . \\ \end{pmatrix}$$

Using $\text{(1)}$ we add up the entries in each row,

$$\begin{pmatrix} 1 \\ \frac{1}{2} \\ \frac{1}{4} \\ \frac{1}{8} \\ \frac{1}{16} \\ . \\ . \\ . \\ \end{pmatrix}$$

And now we add up the entries of our column vector, giving

$\quad \text{ANS: } 2$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.